Sox6 and ALDH1A1 Truncation by Asparagine Endopeptidase Defines Selective Neuronal Vulnerability in Parkinson's Disease - Shuke Nie; Bowei Li; Mengmeng Wang; Zijun Chen; Jiayan Ren; Zixuan Li; Xinli Xu; Zhengjiang Qian; Zhongyun Xie; Jianxin Han; Zhentao Zhang; Zhaohui Zhang; et al. (Advanced Science)
Abstract Dopaminergic neurons in the substantia nigra pars compacta (SNpc) demonstrate regionally selective susceptibility in Parkinson's disease (PD) compared to those in the ventral tegmental area (VTA). However, the molecular mechanism for this distinct vulnerability remains unclear. Here, it is shown that Legumain, also known as asparagine endopeptidase (AEP), is activated in a subgroup of SRY‐box transcription factor 6 /Aldehyde dehydrogenase 1 family member A1, (Sox6+/ALDH1A1+) neurons in the ventral tier of the SNpc and cleaves Sox6 and ALDH1A1, leading to repression of Special AT‐rich sequence binding protein 1 (Satb1) that is a dimeric/tetrameric transcription factor specifically binding to AT‐rich DNA sequences, and toxic dopamine metabolite accumulation. AEP cuts Sox6 and ALDH1A1 in dopaminergic neurons that project to the locus coeruleus (LC), abolishing Sox6's transcriptive and ALDH1A1's enzymatic activities. Co‐expressing AEP‐truncated Sox6 and ALDH1A1 fragments in 3‐month‐old A53T SNCA transgenic mice accelerates dopamine degeneration, whereas expressing AEP‐resistant Sox6 N336A/N446A and ALDH1A1 N220A mutants alleviates rotenone‐induced PD pathologies. Hence, different circuitries and intrinsic properties of dopaminergic neurons in the SNpc and VTA render differential predispositions in PD.